Chapels in the castle in Kamianets-Podilskyi - Bania, Zbigniew (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
In the texts about the castle in Kamianets-Podilskyi, we find mentions of the St. Stanislaus church located in its courtyard, as well as the Orthodox church. Based on castle inventories from the 16th and early 17th century, it is possible to determine their founders and the hypothetical time of these objects’ construction. The Orthodox church was erected at the end of the 14th century from the foundation of the Lithuanian princes Koryatowicz. The church of St. Stanislaus was built with funds from Jan Potocki at the turn of the 16th and 17th centuries. When Kamianets-Podilskyi came under Turkish occupation, probably at that time, after 1672 the Orthodox church was demolished and the church of St. Stanislaus was turned into a mosque. Ruined, it was demolished after the recapture of Kamianets-Podilskyi by Poland in 1699.